Effect of Spatially Distributed Sequential Stimulation on Fatigue in Functional Electrical Stimulation Rowing - Gongkai Ye; Pirashanth Theventhiran; Kei Masani (IEEE, 2022)
Objective: A critical limitation in clinical applications using functional electrical stimulation (FES) for rehabilitation exercises is the rapid onset of muscle fatigue. Spatially distributed sequential stimulation (SDSS) has been demonstrated to reduce muscle fatigue during FES compared to conventional single electrode stimulation (SES) in single joint movements. Here we investigated the fatigue reducing ability of SDSS in a clinical application, i.e., FES-rowing, in able-bodied (AB) participants. Methods: FES was delivered to the quadriceps and hamstring of 15 AB participants (five female, ten male) for fatiguing FES-rowing trials using SES and SDSS, participants rowed with voluntary arm effort while endeavoring to keep their legs relaxed. Fatigue was characterized by the time elapsed until a percent decrease occurred in power output (TTF), as well as the trial length indicating the time elapsed until the complete stop of rowing. Result: Trial length was significantly longer in SDSS rowing than in SES (t-test, ${p} < 0.01$ , ${d}=0.71$ ), with an average SDSS:SES trial length ratio of 1.31 ± 0.47. TTF $_{SDSS}$ was significantly longer than TTF $_{SES}$ with a median TTF $_{SDSS}$ :TTF $_{SES}$ ratio of 1.34 ranging from 1.03 to 5.41 (Wilcoxon Ranked Sum, ${p} < 0.01$ , ${r}=0.62$ ). No rower experienced a decrease in TTF with SDSS. Conclusion: SDSS reduced fatigue during FES-rowing when compared to SES in AB individuals, resulting in a lengthened FES-rowing period by approximately 30%. Application of SDSS would increase the effectiveness of FES-rowing as rehabilitative exercise for individuals with paralyses.